A descriptive study of the impact and significance of the monobloc chair among selected Filipino employees - Herrera, John Louie P.; Quevedo Ma. Teresa P. (2011.)
This study aimed to examine the impact and significance of the monobloc chair among selected Filipino employees. It is a descriptive study that employed quantitative and qualitative research paradigms. Survey was the primary data collection method of the study and the main instrument was a questionnaire. Twenty (20) employees from the College of Home Economics in the University of the Philippines - Diliman were selected as respondents of the study through convenience sampling. Data collected from the survey were then tabulated, summarized and analyzed. Results showed that in general, the impact and significance of the monobloc chair to the respondents is notable, both as a familiar and provisional piece of furniture. In terms of functionality, the monobloc chair was seen as a highly functional and multi-purpose furniture: the most significant aspects of its functionality were portability and stackability. Together with affordability, these were the top three most important characteristics of the monobloc. The chair was moderately accepted by the respondents and received a low rating in terms of value, which can be explained by the respondents' view of it as an inferior kind of furniture compared to those made of other materials. Durability and appearance overtime were the main issues raised by the respondents concerning the chair. The respondents' overall attitude towards the monobloc chair was neutral. However, in terms of their over-all perception, majority of the respondents expressed positive remarks about the chair.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Chairs